Physiological basis of yield reduction with stage-specific moisture stress in groundnut (Arachis hypogaea L.): PHYSIOLOGICAL BASIS OF YIELD REDUCTION WITH STAGE-SPECIFIC MOISTURE STRESS IN GROUNDNUT - C RADHA KUMARI; B SAHADEVA REDDY; M VIJAY SANKAR BABU (Journal of Oilseeds Research, 2026)
A field study was conducted to assess the effect of moisture stress imposed at different growth stages on dry matter partitioning, physiological traits, and pod yield of groundnut. Four moisture regimes-early (30-50 DAS), mid (50-70 DAS), late (70-90 DAS) stress, and stress-free-were evaluated using five varieties (K-6, K-9, Dharani, Anantha, and Harithandhra) under rainout shelters. Results showed that total dry matter, leaf area index (LAI), pods per plant, and pod yield declined significantly under stress, with the greatest reduction under late-stage drought. Pod yield decreased by 15-32% under early stress and up to 87% under late stress. Varieties Dharani and K-9 exhibited superior tolerance by maintaining higher LAI, dry matter, and pod weight. Regression and correlation analyses revealed strong positive relationships between pod yield, dry matter, and LAI, indicating their potential as key selection traits for drought tolerance in groundnut.